Service Quality Based on SERVQUAL Dimension and Its Impact on Customer Satisfaction at Dzahira Medika Clinic - Lusi Olis Vera; Ummu Artha Tsary Rumalessin; Redi Alamsyah (STIE Amkop Makassar, 2025)
This study seeks to determine service quality based on SERVQUAL dimension — tangibles, reliability, responsiveness, assurance, and empathy — and its impact on customer satisfaction at Dzahira Medika Clinic. This sort of research employs a quantitative methodology. This study employs a descriptive approach. The population in this study was an average of 20 patients of Dzahira Medika Clinic per day, while this study was conducted for 7 days, the research sample was 104 people obtained from the Slovin formula. This study gathered primary data by administering a questionnaire to respondents that used a 1–5 point Likert scale. Data analysis was performed with the assistance of IBM SPSS Statistics version 27 software. The Research reveal that Service Quality based on SERVQUAL dimension — tangibles, reliability, responsiveness, assurance, and empathy —has a positive and significant impact on Customer Satisfaction at Dzahira Medika Clinic. This study provides an understanding of how service quality impact customer satisfaction at Dzahira Medika Clinic. The five SERVQUAL dimensions work synergistically to enhance customer satisfaction at Dzahira Medika Clinic. This finding provides valuable insight for management to improve customer satisfaction through good service quality.